Krzysztof Michalski (ed.): Conditions of European Solidarity. Vol. 1. What Holds Europe Together? Vol. 2. Religion in the New Europe.: Central European University Press, Budapest – New York 2006, 192 + 146 s. - Nešpor, Zdeněk R. (Lidé města, 2008)
A review of the book by Krzysztof Michalski.